2018
DOI: 10.21307/ane-2018-024
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone enhancement during pregnancy influences social coping and gene expression of oxytocin and vasopressin in the brain of adult rats

Abstract: Steroid hormones are important mediators of prenatal maternal effects and play an important role in fetal programming. The aim of our study was to investigate how testosterone enhancement during pregnancy influences neurobehavioral aspects of social coping of rat offspring in adulthood. Pregnant rat dams were exposed to depot form of testosterone during the last third of pregnancy (i.e., beginning on the 14 th day of pregnancy). Their adult offspring were later tested in a social interaction test and expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
(60 reference statements)
0
4
0
1
Order By: Relevance
“…In 1993, Broad et al [24] demonstrated that pregnant sheep exposed to progesterone had more OT mRNA in the paraventricular and supraoptic nuclei of the hypothalamus, while those exposed to estrogen didn't show significant growth in the supraoptic nuclei. However, testosterone enhancement during pregnancy brought about decreased oxytocin mRNA expression in the paraventricular nuclei of pregnant rats [25]. Estrogen and testosterone may play an opposite role in the central OT system.…”
Section: Female Reproductive Tissuesmentioning
confidence: 89%
“…In 1993, Broad et al [24] demonstrated that pregnant sheep exposed to progesterone had more OT mRNA in the paraventricular and supraoptic nuclei of the hypothalamus, while those exposed to estrogen didn't show significant growth in the supraoptic nuclei. However, testosterone enhancement during pregnancy brought about decreased oxytocin mRNA expression in the paraventricular nuclei of pregnant rats [25]. Estrogen and testosterone may play an opposite role in the central OT system.…”
Section: Female Reproductive Tissuesmentioning
confidence: 89%
“…According to some research findings (Auyeung et al, 2009; Bakker‐Huvenaars et al, 2018; Xu et al, 2013), autism spectrum disorders are associated with increased testosterone and decreased oxytocin, whereas psychotic affective disorders like schizophrenia are associated with increased oxytocin and decreased testosterone (Crespi, 2016). The oxytocin and testosterone systems interact directly on a molecular and physiological level in humans and rats, leading to opposite, antagonistic responses (Dai et al, 2017; Dzirbíková et al, 2018; Khan et al, 2018; Nicholson & Jenkin, 1995). None of the aforementioned investigations, however, investigated the social behaviour patterns or human brain.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the results of the most recent studies indicate the lowered oxytocin and increased testosterone levels in the placenta of mothers with offspring who developed ASD [55]. Animal models and studies on humans provide the data indicating that increased testosterone levels during pregnancy negatively affect the levels of oxytocin and increases the risk of ASD [56], which might be partially associated with a more frequent incidence of ASD in male children [57].…”
Section: Discussionmentioning
confidence: 99%
“…Dodatkowo wyniki badań wskazują na zmniejszony poziom oksytocyny i zwiększony poziom testosteronu w łożyskach matek u potomstwa, u którego rozwinął się ASD [55]. Zwierzęce modele i badania na ludziach również dostarczają dowodów na to, że zwiększony poziom testosteronu w ciąży wpływa negatywnie na poziom oksytocyny i zwiększa prawdopodobieństwo rozwoju ASD [56], co po części może tłumaczyć częstsze występowanie ASD u dzieci płci męskiej [57].…”
Section: Dyskusjaunclassified